The value of ICG-guided left colon vascular variation and anatomical rules for the radical resection of proctosigmoid colon cancer - Wang, Jiahao; Xie, Jiaxin; Lu, Xinquan; Lin, Jiaxin; Liao, Weilin; Yi, Xiaojiang; Feng, Xiaochuang; Zhu, Bosen; Li, Wenjuan; Tang, Xin; Ao, Lin; Chen, Zhifeng; et al. (Frontiers in Oncology, 2023)
During laparoscopic radical resection for proctosigmoid colon cancer (PCC), surgeons could inadvertently damage the arteries when following the operation path. This study investigated the variations in left colon blood vessels in order to guide the scientific protection of the marginal artery (MA) during laparoscopic surgery for PCC. Data from seven patients who underwent inferior mesenteric artery (IMA) angiography were included as imaging references to preliminarily explore the vascular structure and variation in the left colon. The clinical video data of 183 PCC patients were retrospectively analyzed to observe intraoperative MA injury. Meanwhile, a prospective cohort of 96 patients with the same disease underwent intraoperative indocyanine green (ICG) fluorescence imaging of the peripheral sigmoid artery network, the variation of marginal arteries was summarized, and the distance between vessels and the bowel was measured at different levels. Patients were divided into 'ICG group' and 'non-ICG group' according to whether ICG guidance was performed, and perioperative conditions were compared between the two groups. Taking the integrity of lymph node dissection into consideration, 18 patients underwent carbon nanonode tracing. This study was conducted under the standard consent and ethical approval of the Ethics Committee of our center.7 patients with IMA angiography shared some vascular structures, defined as 'Dangerous Triangle' and 'Secure Window'. Through intraoperative observation, the primary arch was typically located 4.2 (2.3-6.0) cm away from the intestinal canal, and 5.21% (5/96) patients had poor anastomosis at the primary arch. Moreover, secondary vascular arches (6.4 (4.6-10.0) cm from the intestinal wall) were observed in 38.54% of patients. MA injury was identified in 2 of 183 cases, and the ischemic bowel was timely dissected, whereas no such injury occurred during ICG fluorescence-guided surgery. Guided by carbon nanoparticles, the integrity of lymph node dissection can be maintained while preserving the secondary arch in all patients. This study demonstrated the benefits of ICG guidance in protecting the intestinal blood supply in laparoscopic PCC surgery. By enhancing the understanding of primary and secondary vascular arches, secure windows, and dangerous triangles, surgeons can safely optimize the surgical path during surgery.